Does good governance mitigate the ESG risks of tax avoidance? An analytic network process study of Indonesian corporations - Dian Sulistyorini Wulandari; Agus Fuadi; Nadia Fathurrahmi Lawita; Salmiya Kartika Herira; Putri Edelweis Aprilia Alfansyah (Pusat P2M Politeknik Negeri Batam, 2026)
This study investigates whether effective corporate governance mitigates Environmental, Social, and Governance (ESG) risks arising from corporate tax avoidance in Indonesian listed firms. Employing the Analytic Network Process (ANP), this research analyzes expert judgments from six professionals, including the Chairperson of the Indonesian Institute of Accountants (IAI KAPD) Jakarta Region and five members of the IAI Central Office. The analysis is structured around four key criteria: Tax Avoidance, ESG Stability, Corporate Governance, and External Pressure. The findings indicate that corporate governance mechanisms, particularly audit quality and board independence, play a dominant role in mitigating ESG risks associated with aggressive tax behavior. High levels of tax avoidance are found to erode corporate reputation and weaken stakeholder trust, especially in the presence of strong investor and media scrutiny. This study contributes to the literature in three main ways. First, it extends ESG and tax avoidance research by integrating a network-based decision-making approach (ANP), offering a more holistic understanding of interdependencies among governance, fiscal behavior, and sustainability outcomes. Second, it provides empirical evidence from an emerging market context, where institutional pressures and governance structures differ significantly from those of developed economies. Third, it highlights the critical moderating role of governance quality in aligning corporate tax practices with ESG principles. From a practical perspective, the findings imply that regulators and firms should strengthen governance frameworks to promote tax transparency and accountability. Enhancing audit quality and board independence can serve as effective mechanisms to reduce ESG-related risks and support sustainable financial performance. Ultimately, this study underscores the importance of ethical tax practices as a strategic component of ESG resilience in developing economies.